CHARACTERIZATION OF JULY 17, 2006 TSUNAMIITE AT SOUTH COAST OF WEST JAVA - Hendra Amijaya∗; Ngisomuddin Ngisomuddin; Akmaluddin Akmaluddin (Geological Engineering Department Universitas Gadjah Mada, 2015)
July 17, 2006 tsunami which occurred in Indian Ocean had swept most of the south coast of Java, especially at Pangandaran area, West Java. The tsunami wave transported and deposited sediment known as tsunamiite, with various compositions. Three different textural characteristics have been recognized on the tsunami sediment deposit. First type is on the tsunamiite found at West Pangandaran Beach, which is darker than the older beach sediment and separated by erosional surface. The sedimentary structures are parallel lamination and current ripple. The grains have no fining trend in vertical as well as lateral direction. Whereas the second type is found at East Pangandaran Beach, which is brighter than the older beach sediment and also separated by erosional surface. The sedimentary structures are cross lamination on the lower layer, parallel lamination on the middle layer and massif on the upper layer. The grains have no fining trend in vertical and lateral direction Benthic foraminifera is one of organism which is transported and deposited as tsunami deposit on the coast. Ammonia beccarii, Elphidium advenum, Amphistegina lessonii, Cibicides sp., Biginerina irregularis, Bolivina plicata, Bathysiphon sp., Nodosaria andQuinqueloculina were found in the recent tsunami deposit from Pangandaran. Based on the benthic foraminifera contents, it can be inferred that the sediments came from lagoonal until deep sea (abyssal) environment.